Prevalência dos principais vírus respiratórios em bovinos da raça holandesa, no estado do Paraná - Sponchiado, Daniella [UNESP] (2014)
A serological survey of the following respiratory viruses: Bovine Herpesvirus 1 (BoHV-1), Bovine Viral Diarrhea Virus (BVDV), Bovine Parainfluenza Virus Type 3 (bPIV-3) and Bovine Respiratory Syncytial Virus (BRSV) in Holstein cattle black and White (HPB), raised in Paraná state was performed. 714 blood samples were collected from the jugular vein of cattle not vaccinated for the studied agents, over six months of age, from 26 dairy herds, distributed in 17 municipalities of Paraná state. Alongside the collection, a questionnaire was used for each property studied in order to assess the risk factors associated with the viruses examined. The serum samples were subjected to the diagnosis test of virus neutralization at the Laboratory of Viral Diseases of Cattle of the Biological Institute of São Paulo. Frequencies of 22.3%; 35.8%; 80.4% and 93.5% of seropositive cattle were observed and 65.3%, 88.5%, 96.1% and 100% of the seropositive properties BoHV-1, BVDV, bPIV-3 and BRSV, respectively. The co-infection that occurred most frequently was the bPIV-3 and BRSV (37.1%). After logistic regression analysis, risk factors associated with BoHV-1 were cattle with more than 48 months of age (OR = 15.012; 95% CI 7.500 to 30.051), property area 26-50 hectares (OR = 11.328; 95% CI 2.482 – 51.697), stocking higher than three animals per hectare (OR = 1.026; 95% CI 0.370 to 2.847), cattle entry percentage higher than 10% (OR = 52.520 entry; 95% CI 13.269 to 207.876); for BVDV were cattle older than 48 months (OR = 4.407; 95% CI 2.456 to 7.906), Southwest region (OR = 52.388; 95% CI 4.629 to 5892.873), semi-intensive production system (OR = 1.333; 95% CI 0.261 to 6.815),property with fewer animals than or equal to 50 (OR = 16.682; 95% CI 3.218 to 86.481), a percentage of cattle entry higher than 10% (OR = 17.56; 95% CI 7.613 – 40.506) and neighboring pasture sharing (OR = 9.148; 95% CI 3.751 to 22.310); for bPIV-3 cattle older than 48 months ...